OBM funciona? uma meta-análise de artigos publicados na área - Careli, Gabriel Gonçalves (2013)
The purpose of this research was to show, based on an article review if the interventions published on the JOBM had been effective. All the intervention articles published on the JOBM between 1977 and 2011 were reviewed and analyzed according to criteria of consistency and change magnitude. Consistency shows us if the change that accompanied the interventions happened systematically. Magnitude indicates the amount of change that accompanied each intervention. 118 articles were identified as having consistent interventions among the 154 included in the research from the 192 initial selection. Furthermore it was identified that in 78 articles the intervention was accompanied by growth (progression) on the variables and these obtained results between 1.29% and 7133.33% with great concentration of results between 100% and 1000% of growth. Also it was found that in 43 of the articles where decay (regression) in the variables has accompanied the intervention theses varied between 2.70% and 100% with no apparent concentration. The results indicate that most part of the published interventions were accompanied by consistent results with relevant magnitude